On some \(BV_σ\) I-convergent sequence spaces defined by modulus function - Khan, Vakeel.A.; Esi, Ayhan; Shafiq, Mohd (Global Journal of Mathematical Analysis, 2014)
In this article we introduce and study \(_0BV^I_σ(f)\), \(BV^I_σ(f)\) and \(_∞BV^I_σ(f)\) sequence spaces with the help of \(BV_σ\) [see [23]] and a modulus function f. We study topological, algebraic properties and some inclusion relations on these sequence spaces.